Strategi Contexual Teaching and Learning (CTL) pada pendidikan akhlak era distrubsi - Ngadiyo Ngadiyo (At Turots: Jurnal Pendidikan Islam, 2023)
The implementation of "Contextual Teaching and Learning (CTL) Strategy in Moral Education during the Era of Disruption" is presented as a relevant approach in shaping students' character and morality amidst the challenges posed by technological and informational changes. CTL emphasizes the importance of connecting moral education to students' everyday life context, enabling ethical values to be easily understood, internalized, and applied in practice. This article outlines the stages of CTL strategy in moral education, including identifying morally relevant values within the era of disruption, recognizing students' life contexts, integrating moral values into contextual activities, and reflecting and evaluating the outcomes. Supporting theories such as Social Constructivism, Value Theory, Social Learning Theory, and Adult Reflection Theory are utilized to endorse and comprehend the relevance of CTL strategy in moral education. Despite the numerous advantages of CTL, such as its relevance and student-centered approach that fosters character development, the article also acknowledges certain shortcomings that require attention, such as the potential inefficiency in time management and striking a balance between context and curriculum content. Addressing challenges related to assessing and measuring students' moral and character growth is also highlighted as crucial in implementing CTL. In conclusion, the Contextual Teaching and Learning (CTL) strategy offers a compelling alternative to tackle the challenges of moral education during the era of disruption. With proper implementation and effective evaluation, CTL holds the potential to shape students' character and morality more effectively and contextually amidst the ongoing changes and disruptions. Thus, CTL proves to be a valuable approach in enhancing the quality of moral education in the future.